BANGUN SEJAHTERA: STRATEGI KEBANGKITAN EKONOMI PASCA-PHK MELALUI PEMBERDAYAAN SDM BERDAYA SAING DAN LITERASI KEUANGAN - Firly Irhamni; Salwa Robul Izzah; Virsa Najelina Maylaffayza; Lusy Rahmawati (Jurnal Abdi Insani, 2026)
The Open Unemployment Rate (OUR) in Sidoarjo Regency reached the highest in East Java at 6.49% as of August 2024, underscoring the urgency of enhancing local human resource competencies. In Kragan Village, there is a lack of integrated development programs specifically addressing post-layoff recovery and MSME advancement social resilience of individuals and their families (Muqsith & Abidin, 2023). In response, this community service program was designed as a proactive intervention to build economic resilience in Kragan Village, Sidoarjo, a community heavily impacted by job losses. Utilizing a Participatory Action Research (PAR) approach, the program integrated three key thematic training modules: financial literacy, human resource empowerment, and digital marketing. The methodology engaged community members—including the Village Head, the PKK Women's Group, and the Karang Taruna Youth Organization—as active collaborators in a phased intervention. Quantitative pre- and post-test data from 15 participants showed a substantial increase in knowledge, with average scores rising from 45.67 to 82.67 (p<0.001). This finding, supported by qualitative insights from group discussions and a positive perception survey, demonstrates the program’s effectiveness in enhancing participants’ understanding and capabilities. The findings highlight that a collaborative and practical training model can significantly boost community members' confidence and skills in managing personal finances, pursuing new employment opportunities, and launching micro-enterprises. The program successfully enhanced human resource capacity and digital literacy in Kragan Village. This integrated program proved effective in stimulating community-based economic self-reliance.